Detection of Entamoeba histolytica by recombinase polymerase amplification (2015)
Amebiasis is an important cause of diarrheal disease worldwide and has been associated with childhood malnutrition. Traditional microscopy approaches are neither sensitive nor specific for Entamoeba histolytica. Antigen assays are more specific, but many cases are missed unless tested by molecular methods. Although polymerase chain reaction (PCR) is effective, the need for sophisticated, expensive equipment, infrastructure, and trained personnel limits its usefulness, especially in the resource-limited, endemic areas. Here, we report development of a recombinase polymerase amplification (RPA) method to detect E. histolytica specifically. Using visual detection by lateral flow (LF), the test was highly sensitive and specific and could be performed without additional equipment. The availability of this inexpensive, sensitive, and field-applicable diagnostic test could facilitate rapid diagnosis and treatment of amebiasis in endemic regions. Copyright © 2015 by The American Society of Tropical Medicine and Hygiene.